The Roles and Symbolism of Mangupa in Sipirok Traditional Wedding Ceremony - Irmayanti Irmayanti (Journal of English Language Teaching and Linguistics, 2017)
This paper qualitatively examines the roles and symbolism of mangupa in Sipirok wedding ceremony. Results revealed that the presence of piramanuk na dihobolan ( boiling eggs), manuk (chicken), hambeng ( goat meat), and horbo (buffalo meat) in the Sipirok wedding ceremony bring a symbolic meaning for the hosts, bridegroom, their family and guests. Symbolizing of fertility, appreciation, sweet life to the bridegroom, blessing, creating strong bonding, good relationships between guests and marriage declaration are some of the significant on the present those mangupa in the  Sipirok wedding. Hence, it is vital for Sipirok especially the young generation to appreciate and preserved these practices.